Synthesis of α,β-unsaturated esters via a chemo-enzymatic chain elongation approach by combining carboxylic acid reduction and Wittig reaction - Duan, Yitao; Yao, Peiyuan; Du, Yuncheng; Feng, Jinhui; Wu, Qiaqing; Zhu, Dunming (Beilstein journal of organic chemistry, 2015)
α,β-Unsaturated esters are versatile building blocks for organic synthesis and of significant importance for industrial applications. A great variety of synthetic methods have been developed, and quite a number of them use aldehydes as precursors. Herein we report a chemo-enzymatic chain elongation approach to access α,β-unsaturated esters by combining an enzymatic carboxylic acid reduction and Wittig reaction. Recently, we have found that Mycobacterium sp. was able to reduce phenylacetic acid ( 1a ) to 2-phenyl-1-ethanol ( 1c ) and two sequences in the Mycobacterium sp. genome had high identity with the carboxylic acid reductase (CAR) gene from Nocardia iowensis . These two putative CAR genes were cloned, overexpressed in E. coli and one of two proteins could reduce 1a . The recombinant CAR was purified and characterized. The enzyme exhibited high activity toward a variety of aromatic and aliphatic carboxylic acids, including ibuprofen. The Mycobacterium CAR catalyzed carboxylic acid reduction to give aldehydes, followed by a Wittig reaction to afford the products α,β-unsaturated esters with extension of two carbon atoms, demonstrating a new chemo-enzymatic method for the synthesis of these important compounds.